Transformasi Pendidikan Islam di Era Digital: Rekonstruksi Paradigma dalam Perspektif Pemikiran Islam Kontemporer - Aswan Daulay; Febi Ayunda Sari; Ahmad Nasir Sitorus; Ilham Fadhillah Sitorus (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2026)
The digital era has significantly transformed global education systems, including Islamic education. This transformation is not limited to technological adaptation but also requires a fundamental reconstruction of educational paradigms to ensure relevance, sustainability, and value orientation. This article aims to analyze the transformation of Islamic education in the digital era through the lens of contemporary Islamic thought. Using a qualitative approach and library research method, this study examines relevant literature on Islamic educational reform and contemporary intellectual discourse. The findings indicate that contemporary Islamic thought emphasizes three essential dimensions of transformation: the integration of knowledge, epistemological renewal, and the strengthening of ethical and moderate values in digital learning environments. Therefore, the transformation of Islamic education should go beyond mere digitalization and instead involve a comprehensive paradigm shift grounded in Islamic principles and humanistic values. Such reconstruction is expected to produce adaptive, critical, and morally responsible learners capable of responding to the challenges of the digital age.